2012
DOI: 10.1111/j.1440-1797.2012.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐apoptotic and anti‐oxidant effects of grape seed proanthocyanidin extract in preventing cyclosporine A‐induced nephropathy

Abstract: We demonstrated that GSPE prevents CsA nephropathy and that this effect is achieved by anti-apoptotic and anti-oxidant activity. We also achieved a significant recovery in kidney functions without affecting CsA plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 26 publications
2
29
0
2
Order By: Relevance
“…Ulusoy et al have shown that grape seed increased TAS level and decreased TOS level in cyclosporine A-induced nephropathy. 20 In accordance with the findings of our study, Li et al 23 reported antioxidant features of grape seed in STZ-induced diabetic rats. Grape seed proanthocyanidin extract (GSPE) was shown to increase glutathione levels in pancreatic tissue of diabetic rats, resulting in decreased lipid peroxidation, and increased insulin sensitivity by directly affecting the insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 81%
“…Ulusoy et al have shown that grape seed increased TAS level and decreased TOS level in cyclosporine A-induced nephropathy. 20 In accordance with the findings of our study, Li et al 23 reported antioxidant features of grape seed in STZ-induced diabetic rats. Grape seed proanthocyanidin extract (GSPE) was shown to increase glutathione levels in pancreatic tissue of diabetic rats, resulting in decreased lipid peroxidation, and increased insulin sensitivity by directly affecting the insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 81%
“…For the labeling of apoptotic cells, all paraffin-embedded tissue samples were cut into 4-m sections. Terminal deoxynucleotidyltransferase (TdT)-mediated dUTP-biotin nick end labeling (TUNEL) staining of sections was performed by using a standard TUNEL kit (Roche, Mannheim, Germany), in accordance with the manufacturer's instructions (11). Color was then developed with a kit containing 3,3=-diaminobenzidine (DAB) (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Grape seed proanthocyanidin extract (GSPE) is a natural molecule obtained from grape seeds that has many health benefits, including antioxidant, antiapoptotic, anticarcinogenic, and anti-inflammatory properties (8). Previous studies in our clinic have shown the organ-protective effects of this molecule in several acute kidney injury models, but its protective effect against nephropathy secondary to colistin treatment has not yet been investigated (9)(10)(11).…”
mentioning
confidence: 99%
“…ÜÇPÖ'nün inivivo ve invitro çalışmalarda Vitamin C, E ve Beta karotenden daha etkili antioksidan etkili olduğu gösterilmiştir [13]. Daha önce kliniğimizde yapmış olduğumuz çeşitli nefropati ve kardiotoksisite modellerinde ÜÇPÖ'nün antioksidan ve antiapoptotik yolla organ koruyucu etkilerini gösterdik [6][7][8][9]. Yapılan bir klinik çalış-mada ise 5 haftalık ÜÇPÖ tedavisi sonrası hipertansif ratlarda NO üretimini arttırarak antihipertansif etki sağlanıldığı gös-terilmiştir [10].…”
Section: Discussionunclassified
“…ÜÇPÖ'nün reaktif oksijen türlerinin çöpçü-sü ve antioksidan özelliği yanında vazodilatatör, antikarsinojenik, antialerjik, antiinflamatuvar, antibakteriyel, kardiyoprotektif, immunmodulatuvar ve antiviral özelliği çeşitli deneysel çalış-malarda gösterilmiştir [6,7]. Daha önce kliniğimizde yapmış olduğumuz çalışmalarda ise ÜÇPÖ'nün amikasin aracılı nefropati, kontrast madde ilişkili nefropati, siklosporin ilişkili nefropati ve kardiyotoksisiteyi önlemede antioksidan, antiapoptotik ve organ koruyucu etkilerini gösterdik [6][7][8][9]. Cui ve arkadaşlarının yapmış olduğu çalışmada ise ouabain-induced hipertansif ratlarda 5 haftalık ÜÇPÖ verilmesi sonrası NO düzeyini arttırarak antihipertansif etki sağlandığı gösterilmiştir [10].…”
Section: Introductionunclassified